PERAN PEMUDA SEBAGAI AGEN OF CHANGE DALAM GEREJA BERDASARKAN MATIUS 5:13-16 - Chlaudea Mangoting; Mitra Gabriella Kombong, Rismayuni Sarah Londong, Minarianti Tandi Ra'ba, Yanti Arrang (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research aims to explore and understand the role of youth as agents of change in the church context, focusing on the teachings of Jesus in Matthew 5:13-16. The study will analyze how youth can become the "salt of the earth" and the "light of the world," as well as the concrete impact resulting from their role as agents of change within the church. The research methodology employs a qualitative approach, utilizing exploratory studies. Data will be collected through literature review, Bible text analysis, specifically Matthew 5:13-16. Data analysis will use an inductive approach to identify patterns, themes, and concepts emerging from the research findings. The results of this research are expected to provide a deeper understanding of how youth can act as agents of change within the church context. The theological and practical implications of youth's role in reflecting Christ's values in society will be discussed, including specific ways youth can strengthen the church's testimony and have a positive impact on the surrounding community.